2014
DOI: 10.1039/c4nr05739b
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Ni nano-alloy: mixed, core–shell or Janus nano-particle?

Abstract: Bimetallic nanoparticles like Cu-Ni are particularly attractive due to their magnetic and catalytic properties; however, their properties depend strongly on the structure of the alloy i.e. mixed, core-shell or Janus. To predict the alloy structure, this paper investigates the size and shape effects as well as the surface segregation effect on the Cu-Ni phase diagram. Phase maps have been plotted to determine the mixing/demixing behavior of this alloy according the particle shape. Cu-Ni nanoalloy can form a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 33 publications
7
86
1
2
Order By: Relevance
“…13, where some degree of intermixing is usually found. This intermixing may be caused by temperature effects.…”
Section: Thermodynamic Stability Of Segregationmentioning
confidence: 98%
See 1 more Smart Citation
“…13, where some degree of intermixing is usually found. This intermixing may be caused by temperature effects.…”
Section: Thermodynamic Stability Of Segregationmentioning
confidence: 98%
“…The transition temperatures between ordered and intermixed patterns can be compared to the results of the work by Guisbiers et al, 13 in which phase diagrams for 4 nm-sized nanoparticles of several shapes were calculated by thermodynamic modeling, finding transitions at 200, 400 and 400 K for Dh, Ih and fcc shapes respectively. The results for Ih and fcc nanoalloys are in good agreement with our findings, considering that our clusters have a smaller size, circa 2.5 nm, and thus are expected to present somewhat lower transition temperatures.…”
Section: Thermodynamic Stability Of Segregationmentioning
confidence: 99%
“…Nonetheless, this effect is small, and this is in agreement with the predictions made for similarly shaped PtPd nanoparticles with a radius of 4 nm. 8,9,53 We would like to stress that if a structure is very unfavourable for a given chemical composition, it will rearrange toward a more stable shape before melting. We have found that the thermodynamic approach gives important and useful insights into the thermal behaviour of nanoparticles with a radius above 3-4 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature dependent chemical order (or ''compositional structure''), namely, the equilibrium atomic distribution of the two elements among the different surface and core sites of the NP, affects considerably its physical and chemical properties. 10 Recently, atomic site-specific chemical order in fcc-based 201-and 586-atom Pt-Ir truncated-octahedron (TO) nanoparticles was studied 11 by us using near-surface coordinationdependent bond-energy variations (CBEV) 12 as input to the statistical-mechanical free-energy concentration expansion method (FCEM), 13 which takes into account analytically short-range order. Thus, in Cu, Ni or Co alloyed with Ag, the formation of side-separated ''Quasi-Janus'' configurations was attributed to the near-surface elastic strain release using the Gupta potential and computational global optimization.…”
Section: Introductionmentioning
confidence: 99%